Synthesis and Characterization of a NiCo2O4@NiCo2O4 Hierarchical Mesoporous Nanoflake Electrode for Supercapacitor Applications - Xin Chen (Nanomaterials, 2020)
In this study, we synthesized binder-free NiCo2O4@NiCo2O4 nanostructured materials on nickel foam (NF) by combined hydrothermal and cyclic voltammetry deposition techniques followed by calcination at 350 °C to attain high-performance supercapacitors. The hierarchical porous NiCo2O4@NiCo2O4 structure, facilitating faster mass transport, exhibited good cycling stability of 83.6% after 5000 cycles and outstanding specific capacitance of 1398.73 F g−1 at the current density of 2 A·g−1, signifying its potential for energy storage applications. A solid-state supercapacitor was fabricated with the NiCo2O4@NiCo2O4 on NF as the positive electrode and the active carbon (AC) was deposited on NF as the negative electrode, delivering a high energy density of 46.46 Wh kg−1 at the power density of 269.77 W kg−1. This outstanding performance was attributed to its layered morphological characteristics. This study explored the potential application of cyclic voltammetry depositions in preparing binder-free NiCo2O4@NiCo2O4 materials with more uniform architecture for energy storage, in contrast to the traditional galvanostatic deposition methods.